Harnessing harmony music, power, and politics in the United States, 1788-1865 - Coleman, Billy (The University of North Carolina Press, 2020)
"'Harnessing harmony' uses music to unravel the relationship between elite power and the people through their uses of culture in politics from the early national period to the Civil War. Coleman traces how understandings of musical power were used to shape the development of a popular American political culture. It explores primarily how elites, at a time of mass democratization and rapid social change, looked to music to persuade Americans to rise above political and partisan conflict to instead create a more unified, orderly, and deferential society. In doing so the work identifies a distinctively conservative strain of musical thought and action. As our readers point out, it impressively challenges prevailing scholarly assumptions about political music being more 'bottom up' than 'top down'"--